2016
DOI: 10.1590/0100-3984.2015.0078
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary infection caused by Mycobacterium kansasii: findings on computed tomography of the chest

Abstract: ObjectiveTo describe the main tomography findings in patients diagnosed with pulmonary infection caused by Mycobacterium kansasii.Materials and MethodsRetrospective study of computed tomography scans of 19 patients with pulmonary infection by M. kansasii.ResultsOf the 19 patients evaluated, 10 (52.6%) were male and 9 (47.4%) were female. The mean age of the patients was 58 years (range, 33-76 years). Computed tomography findings were as follows: architectural distortion, in 17 patients (89.5%); reticular opaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
14
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 25 publications
2
14
2
Order By: Relevance
“…In conclusion, Mogami et al ( 11 ) reported chest CT findings that could help radiologists suspect of M. kansasii infection and include this condition in the differential diagnosis.…”
mentioning
confidence: 92%
See 3 more Smart Citations
“…In conclusion, Mogami et al ( 11 ) reported chest CT findings that could help radiologists suspect of M. kansasii infection and include this condition in the differential diagnosis.…”
mentioning
confidence: 92%
“…In the study conducted by Mogami et al. ( 11 ) bronchiectasis occurred more often in the upper lobes, suggesting that radiologists should be aware of atypical manifestations of MTN infection.…”
mentioning
confidence: 94%
See 2 more Smart Citations
“…Chest CT has been shown to be the imaging exam of choice for the evaluation of thoracic diseases ( 6 - 9 ) , as well as for that of diseases of the tracheobronchial tree ( 10 - 12 ) . In individuals with amyloidosis, a CT scan can reveal smooth or irregular/nodular thickening of the tracheal wall and bronchi, which can be accompanied by calcified nodules in the submucosa ( 4 ) .…”
mentioning
confidence: 99%